An introduction to systems biology : design principles of biological circuits - Alon, Uri, ....- (Boca Raton (Fla.) : Chapman & Hall/CRC, 2007)
An Introduction to Systems Biology: Design Principles of Biological Circuits builds a solid foundation for the intuitive understanding of general principles. It encourages the reader to ask why a system is designed in a particular way and then proceeds to answer with simplified models. Explains the basic circuitry in transcription regulation, signal transduction, and developmental networks Includes examples ranging from bacterial chemotaxis through developmental patterning and neuronal circuits to immune recognition Examines the principle of robustness Details how constrained evolutionary optimization can be used to understand optimal circuit design Considers how kinetic proofreading and other mechanisms can minimize errors made in biological information-processing Includes solved problems after each chapter that detail topics not discussed in the main text Thorough and accessible, this book presents the design principles of biological systems, and highlights the recurring circuit elements that make up biological networks. It provides a simple mathematical framework which can be used to understand and even design biological circuits. The text avoids specialist terms, focusing instead on several well-studied biological systems that concisely demonstrate key principles.
Includes bibliographical references (p. 271-293) and index.
Keywords: Basic Sciences. Biology -- Biosystematics; Biological systems -- Mathematical models; Computational biology; Systems biology